The Goldman Sachs foreign exchange handbook, 1994 (London : Euromoney in association with Goldman Sachs, 1994)
The handbook details the 1994 foreign exchange markets in North America, Africa, Asia, Europe and the United Kingdom.
ne 27/08/2021
Ref.
Keywords: Banks and banking; Foreign exchange; Financial institutions